Guidelines for Standardization and Classification of Hotels in Bhutan / Kunzang Norbu and Manat Chaisawat - Norbu, Kunzang; Chaisawat, Manat (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2011)
Tourism in Bhutan was initiated in 1974 coinciding with the coronation of the fourth King of Bhutan and the policy makers adopted a policy of high value low volume. Against this back ground, the development of the tourism infrastructure remains a high priority, particularly in upgrading the facilities and services of hotels and accommodation within the country. The study therefore attempts to develop guidelines for the hotels that are appropriate, unique and encompass a wholesome and dynamic approach. It covered a total of 44 hotels of the 75 currently registered and includes a focus group meeting. The study identifies the constraints and problems, establishes the cause and effect relationship and concludes that quality standards are not consistent with the policy of high value and low volume. The findings and recommendations pertain to developing professionalism in the hotel industry, improving the quality offood and the need to infuse more innovation in cuisine varieties and upgrading the quality of hotel facilities and services. The study also recommends five category of hotels viz. Standard, Tourist Standard, First Class, Deluxe and Luxury category. All of these improvements will form the basis for the standardization and classification of hotels in Bhutan.